Advanced Manufacturing Technology Implementation Process in SME: Critical Success Factors - Jani Rahardjo; Salleh bin Yahya (Institute of Research and Community Outreach - Petra Christian University, 2010)
The aim of this paper is to present critical factors that constitute a successful implementation of the Advanced Manufacturing Technologies (AMT) in Small Medium Enterprise (SME). Many large companies have applied AMT and the applications have shown significant results in this global market era. Conveniently, these phenomenons are also engaged to Small Medium Enterprises (SME) that of high demands on performing high quality product, fast delivery, reliable and more flexible. The implementation of AMT follow several processes namely pre installation, installation, improvement and mature. In order to guarantee the succesfull of running these processes, one should consider the Critical Success Factors (CSF). We conducted a survey to 125 SMEs that have implemented AMT, and found that the CSF for each process are moderately different. Good leadership is the main critical success factor for preparing and installation of the AMT. Once the AMT started or installed and arrived at growth stage, the financial availability factor turns into a critical success factor in the AMT implementation. In, mature stage, the support and commitment of top management becomes an important factor for gaining successful implementation. By means of factor analysis, we could point out that strategic factors are the main factors in pre-installation and installation stage. Finally, in the growth stage and mature stage, both tactical and strategic factors are the important factors in the successful of AMT implementation